PG42 Simulation as a training tool in a global pandemic. (10th November 2020) - Brewster, Ruth; Hughes, Jonathan; Parke, Tim; Jacques, Andrew
Abstract : Background: With the rising Covid-19 pandemic, it became clear that we would need to dramatically expand our ICU in bed capacity and trained staff. Additional theatre staff became available, but there was very limited time to train them. The 'Covid sims' were developed as a tool to train hundreds of staff in a short space of time, in the week before the pandemic was modelled to escalate in our hospital. Summary of Work: In just one week, over 200 members of theatre, ED and critical care staff attended the 'Covid sims'. The training covered: Demonstration and practice of donning and doffing PPE. Simulation station incorporating adaptations required for intubation and ventilation of the Covid patient, alongside demonstrations of the theatre anaesthetic machines and ICU ventilators. Demonstration and explanation of proning, followed by guided practice. Teamwork; the mix of skill sets of those attending mimicked a team presenting for a shift – ODPs, anaesthetists, physiotherapists, ICU doctors and nurses and critical care outreach staff. This enabled staff to develop their new team roles in a simulated environment prior to the pandemic arriving. Summary of Results: Over 200 members of staff were trained over the course of one week. This enabled the expansion of the ICU across elective theatres, tripling our usual maximum ICU capacity. Feedback from the sims reflected the full range of attendees. Specific aspects mentioned were: development of confidence and competence with practising new skills, standardised training enabling standardised care and facilitating teamwork, addressing knowledge gaps, improved safety, appropriate timing to retain knowledge and skills. Increased confidence and reduced anxiety were universal in the respondants. Discussion and Conclusions: Simulated sessions are an effective way to train a large group of staff with different skill sets in a very short amount of time. From feedback received, staff felt more confident in their own competence, less anxious about what was required of them and more able to meet the challenges of the surge when it happened. Recommendations: The merits of simulation for acquisition of technical skills and improvements in team performance have been demonstrated in multiple prior studies. Despite improvements in confidence and reductions in anxiety not being a primary aim of these simulations, their prevalence was prominent in the feedback, over and above technical skills. It would be of interest to look into this in more detail using semi-structured interviews and a thematic analysis. Reference: Goldshtein D, Krensky C, Doshi S, et al, In situ simulation and its effects on patient outcomes: a systematic review. BMJ Simulation and Technology Enhanced Learning 2020;6:3–9. Rosen MA, Hunt EA, Pronovost PJ, Federowicz MA, Weaver SJ. In situ simulation in continuing education for the health care professions: a systematic review. J Contin Educ Health Prof 2012;32(4):243–254. doi:10.1002/chp.21152